Morphologic and functional scoring of cystic fibrosis lung disease using MRI - Eichinger, Monika; Optažaite, Daiva-Elžbieta; Kopp-Schneider, Annette; Hintze, Christian; Biederer, Jürgen; Niemann, Anne; Mall, Marcus A.; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich; Puderbach, Michael (European journal of radiology, 2012)
Magnetic resonance imaging (MRI) gains increasing importance in the assessment of cystic fibrosis (CF) lung disease. The aim of this study was to develop a morpho-functional MR-scoring-system and to evaluate its intra- and inter-observer reproducibility and clinical practicability to monitor CF lung disease over a broad severity range from infancy to adulthood. 35 CF patients with broad age range (mean 15.3years; range 0.5-42) were examined by morphological and functional MRI. Lobe based analysis was performed for parameters bronchiectasis/bronchial-wall-thickening, mucus plugging, abscesses/sacculations, consolidations, special findings and perfusion defects. The maximum global score was 72. Two experienced radiologists scored the images at two time points (interval 10weeks). Upper and lower limits of agreement, concordance correlation coefficients (CCC), total deviation index and coverage probability were calculated for global, morphology, function, component and lobar scores. Global scores ranged from 6 to 47. Intra- and inter-reader agreement for global scores were good (CCC: 0.98 (R1), 0.94 (R2), 0.97 (R1/R2)) and were comparable between high and low scores. Our results indicate that the proposed morpho-functional MR-scoring-system is reproducible and applicable for semi-quantitative evaluation of a large spectrum of CF lung disease severity. This scoring-system can be applied for the routine assessment of CF lung disease and maybe as endpoint for clinical trials.
Available online 23 March 2011
Gesehen am 11.07.2019